2007
DOI: 10.1093/hmg/ddm074
|View full text |Cite
|
Sign up to set email alerts
|

Restriction landmark genome scanning identifies culture-induced DNA methylation instability in the human embryonic stem cell epigenome

Abstract: Widespread provision of human embryonic stem cells (hESCs) for therapeutic use, drug screening and disease modelling will require cell lines sustainable over long periods in culture. Since the short-term, in vitro culture of mammalian embryos can result in DNA methylation changes, the epigenetic stability of hESCs warrants investigation. Existing hESC lines have been derived and cultured under diverse conditions, providing the potential for programming differential changes into the epigenome that may result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(113 citation statements)
references
References 48 publications
6
104
2
1
Order By: Relevance
“…A small number of loci were altered in a large proportion of MD offspring, suggesting that some changes occur at highly susceptible regions of the genome. The nonrandom susceptibility of some loci to environmental perturbation is similar to our recent observations that, in blastocyst-derived human embryonic stem cells, notably Ͼ80% of the loci altered in undifferentiated cells persisted after differentiation (24). Because we wish to sustain the experimental animals in the current study to determine their later-life disease phenotypes, we have not yet been able to determine whether the methylation changes observed in fetal liver persist into adulthood.…”
Section: Discussionsupporting
confidence: 68%
“…A small number of loci were altered in a large proportion of MD offspring, suggesting that some changes occur at highly susceptible regions of the genome. The nonrandom susceptibility of some loci to environmental perturbation is similar to our recent observations that, in blastocyst-derived human embryonic stem cells, notably Ͼ80% of the loci altered in undifferentiated cells persisted after differentiation (24). Because we wish to sustain the experimental animals in the current study to determine their later-life disease phenotypes, we have not yet been able to determine whether the methylation changes observed in fetal liver persist into adulthood.…”
Section: Discussionsupporting
confidence: 68%
“…[14][15][16][17][18][19] It has also been suggested that epigenetic modifications in cell lines may result from intrinsic factors associated with cell culturing, 4,20 including altered methylation maintenance in response to the availability of methyl donors in the culturing media, 21 and altered methylation over time with increasing passage number. 22 The observed differences in methylation between PBLs and LCLs may also be explained by cell-type specific methylation. LCL DNA samples used in this study were derived from purified B lymphocytes transformed by EBV, while the PBL samples did not undergo such enrichment and represent a range of leukocyte types.…”
Section: Resultsmentioning
confidence: 99%
“…Imprinting refers to a phenomenon in which gene expression is regulated in a parentally specific, epigenetic manner. Although several previous studies have reported the epigenetic instability of in vitro cultured hESCs [29,30], imprinted genes seem less susceptible to in vitro culture conditions [27]. Thus, the expression pattern of imprinted genes in hESCs might faithfully reflect the original imprinting state of the embryo according to the results of a recent study, the error rate is normally 2-5% when using the same high-resolution SNP microarray to analyze hESCs [34].…”
Section: Discussionmentioning
confidence: 97%